Fat crystallization, partial coalescence and melting resistance of ice cream with lauric diacylglycerol oil - Liao, Xintao; Xie, Yiping; Liau, Khai Yi; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Qiu, Chaoying (Elsevier Ltd, 2025)
Lauric acid-rich diacylglycerols (DAG) prepared from coconut oil (CO) and palm kernel stearin (PKST) were applied as lipid materials for ice cream. The influences of emulsifiers: glycerin monostearate (MSG), sucrose esters (S1170 and S1670) on the CO/PKST–DAG crystallization and properties of emulsions were evaluated. The CO/PKST–DAGs showed broad peaks with increased crystallization onsets, and the heterogeneous nucleation sites led to the formation of large crystals. DAG–emulsions presented higher partial coalescence degree but improved physical stability without guar gum addition. The emulsions showed strengthened network and good anti-melting properties with large droplet clusters around air bubbles. Lipophilic MSG promoted interfacial nucleation and increased the partial coalescence degree and emulsion rigidity, whereas S1670 reduced the partial coalescence and accelerated the melting process. CO/PKST-DAG formed fat crystallization network with >1.4 fold higher hardness than those of CO/PKST emulsion. Therefore, the CO/PKST-DAGs are promising lipid materials for fabricating melt-resistance ice creams. The rigidity and melting behavior can be further tailored by different emulsifiers.